PEMBERDAYAAN MASYARAKAT KOTA DENGAN PENGUATAN PENGETAHUAN E-COMMERCE PASCA PANDEMI COVID-19 - Andy Rio Handoko; Dyah Retno Utari (Politeknik Negeri Sriwijaya, 2023)
In an e-commerce situation that is developing very rapidly, the COVID-19 pandemic hit Indonesia and not only had an impact on the public health system but also had an impact on the people's economy. Traders, both small and retail businesses, are feeling the effects of the COVID-19 pandemic, and it is not uncommon for some to go out of business because their income is not proportional to their expenses. Ultimately, this directly or indirectly impacts the economy of the lower middle class. Residents in Pesanggrahan Village, which has a population of approximately 4,300 people with 1,000 families, are one of the affected communities. Most people's livelihoods in RW.03 Pesanggrahan Village are as traders, private employees, and laborers. This Community Service Program is one of the efforts to revive the people's economy affected by the COVID-19 pandemic. This activity aims to provide broader knowledge about e-commerce for the lower middle class affected by the COVID-19 pandemic in the Industrial Age 4.0. The results show that the target community finds the education provided useful and motivates them to strive to restore the economy through entrepreneurshipKeywords: COVID-19 Pandemic, Community Services, E-commerce, Small Medium Enterprise